2011
DOI: 10.1161/circulationaha.110.007021
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Senescence, Vascular Disease, and Aging

Abstract: Longevity is a vascular question, which has been well expressed in the axiom that man is only as old as his arteries. To a majority of men death comes primarilyn 2030, when all of the baby boomer generation will be Ն65 years of age, nearly 1 in 5 US residents is expected to be Ͼ65 years of age. By 2050, this age group is projected to more than double in number, from 38.7 million in 2008 to an estimated 88.5 million (Figure 1). 2 Similarly, the population Ն85 years of age is expected to more than triple, from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
91
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(98 citation statements)
references
References 115 publications
1
91
0
6
Order By: Relevance
“…Careful examination of the coronary arteries in humans with this syndrome show that there are atherosclerotic lesions with cholesterol crystals and activated macrophages, but the degree of lipid accumulation is less and there is more fibrous tissue and calcium in the intima compared with usual plaques. There was also a unique adventitial thickening with pronounced fibrosis that may have contributed to the stenosis (942,1344). Whether impaired endothelial repair leads to this remarkably premature atherosclerosis or some other mechanism is the underlying cause remains unknown.…”
Section: New Insights From Rare Laminopathiesmentioning
confidence: 99%
“…Careful examination of the coronary arteries in humans with this syndrome show that there are atherosclerotic lesions with cholesterol crystals and activated macrophages, but the degree of lipid accumulation is less and there is more fibrous tissue and calcium in the intima compared with usual plaques. There was also a unique adventitial thickening with pronounced fibrosis that may have contributed to the stenosis (942,1344). Whether impaired endothelial repair leads to this remarkably premature atherosclerosis or some other mechanism is the underlying cause remains unknown.…”
Section: New Insights From Rare Laminopathiesmentioning
confidence: 99%
“…Cellular senescence is considered to play a causal role in the pathogenesis and development of vascular aging (Kovacic et al 2011a, b;Minamino and Komuro 2007). Cellular senescence causes disorders of ECM metabolism, initiates vascular remodeling, and finally results in a reduction in compliance and an increase in stiffness (Kovacic et al 2011a;Minamino and Komuro 2007). The circulating level of testosterone decreases with age gradually.…”
Section: Introductionmentioning
confidence: 99%
“…Like other mitotic cells, vascular cells may undergo replicative senescence driven by telomere shortening or stressinduced premature senescence 98,99 ; senescent vascular cells have decreased proliferative and angiogenic capacity. Importantly, oxidative stress has been linked to accelerated telomere shortening, DNA damage, senescence of endothelial and vascular smooth muscle cells, and atherosclerosis.…”
Section: Vascular Agingmentioning
confidence: 99%
“…Importantly, oxidative stress has been linked to accelerated telomere shortening, DNA damage, senescence of endothelial and vascular smooth muscle cells, and atherosclerosis. [99][100][101] Telomere length has been shown to be similar in low birth weight versus control infants assessed at birth 102 ; however, another study demonstrated that telomere length was decreased in 5-year olds that were born with low birth weight, 103 which together suggests accelerated attrition. To our knowledge, the effect of preterm birth on telomere shortening, however, has not been reported.…”
Section: Vascular Agingmentioning
confidence: 99%